Analysis of Information Feedback on Residential Energy Conservation and the Implications: The Case of China - Li, Zhuangai; Cao, Xia (Frontiers in Environmental Science, 2021)
Household electricity consumption has increased significantly over the last two decades, leading to a series of policy interventions targeting to reduce electricity consumption in the residential sector. Information feedback regarding household electricity consumption is considered a cost-effective approach to promoting energy conservation. Various studies have so far covered the effects of information feedback on electricity consumption, yet the variations in both the types of feedback provided and the research methodologies have made it difficult to draw plausible conclusions. In China’s case, less due regard has been given to the effectiveness of various types of information feedback. This study has compared the effectiveness of information feedback between emailing electricity bills to households and installing smart meters in terms of promoting electricity conservation by employing empirical survey data from the Chinese General Social Survey with the help of the propensity score matching method. The results show that information provision via information bills curtails electricity consumption by around 20%, whereas information feedback via smart meters installation has no positive effects on household electricity conservation due to lack of access and knowledge to understand the displays of advanced meters. In light of the above results, the study suggests that policy-makers stress the importance of information feedback-based initiatives and improve the information feedback capacity of smart meters through training and education.